2015
DOI: 10.11131/2015/101182
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analyses of the Nuclear Receptor Superfamily

Abstract: Nuclear receptors (NR) act as an integrated conduit for environmental and hormonal signals to govern genomic responses, which relate to cell fate decisions. We review how their integrated actions with each other, shared co-factors and other transcription factors are disrupted in cancer. Steroid hormone nuclear receptors are oncogenic drivers in breast and prostate cancer and blockade of signaling is a major therapeutic goal. By contrast to blockade of receptors, in other cancers enhanced receptor function is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 134 publications
3
54
0
Order By: Relevance
“…Meanwhile, some glucocorticoids, including PRED, are known to have weak mineralocorticoid activity, whereas others, especially synthetic glucocorticoids such as DEX, betamethasone, and triamcinolone showing insignificant inhibitory effects in the present study, have no such potency . These findings, together with other data demonstrating a significantly lower risk of developing bladder cancer in hypertensive patients treated with a mineralocorticoid receptor (MR) antagonist spironolactone as well as downregulation of MR expression in bladder cancer samples, may indicate the involvement of glucocorticoid‐mediated MR signaling in urothelial tumorigenesis. It is still of importance to determine why most of the glucocorticoids have little or no impact on urothelial tumorigenesis.…”
Section: Discussionsupporting
confidence: 55%
“…Meanwhile, some glucocorticoids, including PRED, are known to have weak mineralocorticoid activity, whereas others, especially synthetic glucocorticoids such as DEX, betamethasone, and triamcinolone showing insignificant inhibitory effects in the present study, have no such potency . These findings, together with other data demonstrating a significantly lower risk of developing bladder cancer in hypertensive patients treated with a mineralocorticoid receptor (MR) antagonist spironolactone as well as downregulation of MR expression in bladder cancer samples, may indicate the involvement of glucocorticoid‐mediated MR signaling in urothelial tumorigenesis. It is still of importance to determine why most of the glucocorticoids have little or no impact on urothelial tumorigenesis.…”
Section: Discussionsupporting
confidence: 55%
“…[296][297][298][299][300] Bootstrapping approaches 301 established that, across cancers, only the NR family was significantly downregulated, but was neither significantly mutated nor altered by copy number variation. 302 Within the NRs, we found that several NRs were uniquely suppressed in only one tumor site, including VDR in the colon cancer (COAD) cohort; this finding may reflect the strong expression of VDR in the normal colon. VDR downregulation was not found to be driven by copy number variation or mutation and thus epigenetic mechanisms may be primarily responsible for altered expression.…”
Section: Author Manuscriptmentioning
confidence: 78%
“…These data are publically available and were downloaded. The data actually include tumors and normal samples and, therefore, we created an expression table of all genes detectable in at least 80% of tumors ( n = 16,785) given as relative Z -scores as compared to the mean of the normal [150]. Expression of the 165 gene-panel of the DNA methylation pathway was examined in this table using to capture only those genes altered by more than two Z -scores in 25% of tumors; this yielded 21 genes on the DNA methylation pathway.…”
Section: Bioinformatic Approaches To Reveal Associations Between Dmentioning
confidence: 99%